2021
DOI: 10.3389/fimmu.2021.675250
|View full text |Cite
|
Sign up to set email alerts
|

CD3+CD4+gp130+ T Cells Are Associated With Worse Disease Activity in Systemic Lupus Erythematosus Patients

Abstract: The receptors for IL-35, IL-12Rβ2 and gp130, have been implicated in the inflammatory pathophysiology of autoimmune diseases. In this study, we set out to investigate the serum IL-35 levels and the surface levels of IL-12Rβ2 and gp130 in CD3+CD4+, CD3+CD4─ and CD3─CD4─ lymphocyte subpopulations in systemic lupus erythematosus (SLE) patients (n=50) versus healthy controls (n=50). The potential T cell subsets associated with gp130 transcript (i.e. IL6ST) expression in CD4+ T cells of SLE patients was also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Interleukin (IL) is a group of cytokines crucial in regulating immune responses such as inflammation as well as mediating immune cells growth, differentiation, activation, and migration. Imbalanced T cell subsets have been identified in SLE patients associated with SLE immunopathogenesis (1)(2)(3)(4)(5). Naïve CD4 + T helper (Th) cells differentiate on activation into various cell subsets, namely Th1, Th2, and Th17, with specific profile of cytokines production and different immunopathological implications.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL) is a group of cytokines crucial in regulating immune responses such as inflammation as well as mediating immune cells growth, differentiation, activation, and migration. Imbalanced T cell subsets have been identified in SLE patients associated with SLE immunopathogenesis (1)(2)(3)(4)(5). Naïve CD4 + T helper (Th) cells differentiate on activation into various cell subsets, namely Th1, Th2, and Th17, with specific profile of cytokines production and different immunopathological implications.…”
Section: Introductionmentioning
confidence: 99%
“…70 Additionally, the enhancer regulating ANKRD55 in our eGRN (chr5:56139147-56162711) was also connected to IL6ST ( Figure 7G ), a gene which has been associated with T cell function and disease activity in SLE. 71 The enhancer overlaps two AD associated peaks downregulated in most ADs we analysed ( Figure 7H ), except for peak chr5:56139295-56140114, which showed a distinct upregulation in Graves’ disease. In line with this, TF activity of HIC2 (previously identified as a transcriptional repressor 72 , and linked to enhancer chr5:56139147-56162711 in our eGRN) was increased in Graves’ disease, while being decreased in psoriasis and SLE ( Figure 7I ).…”
Section: Resultsmentioning
confidence: 86%
“…70 Additionally, the enhancer regulating ANKRD55 in our eGRN (chr5:56139147-56162711) was also connected to IL6ST (Figure 7G), a gene which has been associated with T cell function and disease activity in SLE. 71 The enhancer overlaps two AD associated peaks downregulated in most ADs we analysed (Figure 7H)!"#$%#&'"()*"&#+,"%-*./.012343.5.0167116! "8-9%-" :-)8#;"+";9:'9<%'"=&*#>=?+'9)<"9<"@*+A#:B";9:#+:#C"D<"?9<#"89'-"'-9:!…”
Section: Prioritisation and Validation Of Egrn Enhancers-gene Pairs P...mentioning
confidence: 98%
“…Mohd shukri et al. ( 29 ) also found a similar phenomenon in SLE patients, the level of IL-35 in SLE patients was higher than that in healthy controls, but they did not further observe whether there were differences in IL-35 levels in SLE patients with different disease states.…”
Section: Discussionmentioning
confidence: 91%
“…It is worth noting that the level of IL-35 in IMN patients is always higher than that in healthy controls, whether in remission or active period, suggesting that as an autoimmune disease, IMN patients' autoimmune response remains active, even if the disease is relieved. Mohd shukri et al (29) also found a similar phenomenon in SLE patients, the level of IL-35 in SLE patients was higher than that in healthy controls, but they did not further observe whether there were differences in IL-35 levels in SLE patients with different disease states.…”
Section: Treg Cells Directly or Indirectly Inhibit Immune Response An...mentioning
confidence: 92%